The Influence Of Training And Competence On The Performance Of Civil Servants In The Department Of Women's Empowerment And Child Protection Of South Sumatera Province - Muhammad Ridho Kurniawan; Zunaidah zunaidah; Wita Farla (UNIVED Press, 2025)
This study focuses on the low performance of civil servants at the Women's Empowerment and Child Protection Service of South Sumatra Province, which is caused by the lack of training and understanding in handling issues of violence against women and children. The purpose of this study was to analyze the effect of training and competence on the performance of civil servants at the service. The method used was a survey with multiple linear regression analysis, primary data collection through questionnaires to 40 employees during the period May 2024 to January 2025. The results of the study showed that training and competence had a positive and significant effect on employee performance. This study concludes that increasing employee training and competency development programs can have a positive impact on performance, and it is recommended that the PPPA Service of South Sumatra Province implement relevant and structured training.